An evaluation of the influence of different finishing lines on the fracture strength of full contour zirconia CAD/CAM and heat press all-ceramic crowns - Al-Joboury, Ahmed I; Zakaria, Maan R; J, Mustafa M (Journal of Baghdad College of Dentistry, 2015)
ABSTRACTBackground: One of the major problems of all ceramic restorations is their probable fracture against the occlusal forces. The objective of this in vitro study was to evaluate the effect of two gingival finishing lines (90°shoulder and deep chamfer) on the fracture resistance of full contour CAD/CAM and heat press all-ceramic crowns.Materials and Methods: Thirty two maxillary first premolars were prepared to receive full contour CAD/CAM (zolid) and heat press (Cergo Kiss) ceramic crowns using a special paralleling device (Parallel-A-Prep). The teeth were divided into four groups according to the type of finishing line prepared. Each crown was cemented to its corresponding tooth using self-etch, self-adhesive dual cure resin cement. Following storage for 1 week in distilled water at room temperature, teeth were subjected to thermal cycling. Fracture resistance was determined using a universal testing machine, and the samples were investigated microscopically from the point of view of the origin of the failure. Statistical analysis was carried out using the one-way ANOVA and Student’s t-tests.Results: The mean values of fracture resistance for CAD/CAM group showed 1367.250+178.967 N for 90°shoulder margins and 1109.250+252.455 N for the deep chamfer margins. ANOVA test results revealed high significance between and within the groups. The mean values of fracture resistance for heat press group were 548.562+272.471 N for 90°shoulder margins and 247.912+96.995 N for the deep chamfer margins expressing statistical significance. Conclusions: The results of this study pointed to a relationship between the design of the cervical finishing line and the fracture strength of the full CAD/CAM crowns and the full heat press ceramic crowns. Both 90° shoulder and deep chamfer finishing lines are suitable for zolid crowns while the 90° shoulder is more suitable for the Cergo Kiss crowns than the deep chamfer preparation.Key words: Full contour, All-ceramic crowns, CAD/CAM, Heat press, Fracture strength.